À procura de Moçambique no Museu Nacional de Etnologia, Portugal - Sarmento, João Carlos Vicente (2020)
English version: Sarmento, J., & Martins, M. de L. (2020). Searching for Mozambique at the National Museum of Ethnology, Portugal. Lusophone Journal of Cultural Studies, 7(2), 15-32. https://doi.org/10.21814/rlec.3132